Ausência de arteriosclerose na porção intramiocárdica das artérias coronárias: Um mistério a ser resolvido? - Ramalli Jr, Edvaldo Luiz; Braga, Leonardo Henrique; Evora, Patricia Martinez [UNESP]; Albuquerque, Agnes Afrodite Sumarelli; Celotto, Andrea Carla; Mota, André Lupp; Evora, Paulo Roberto Barbosa (Sociedade Brasileira de Cirurgia Cardiovascular, 2011)
Several studies show that portions of intramyocardial coronary arteries are spared of arteriosclerosis, involving morphological, embryological, biochemical and pathophysiological aspects. Endothelial function is significantly affected in the segment of transition, as estimated by the vasoactive response to Ach. These findings suggest that myocardial bridge can provide protection against arteriosclerosis by counteracting the negative effects of endothelial dysfunction. The intramyocardial portion's protection phenomenon deserves further scientific research on all research fronts. Improved morphological, biomechanical and especially physiological and embryological knowledge may be the key to a future window of opportunity for chronic arterial disease therapy and prevention. In addition, this review discusses possible therapeutic approaches for symptomatic coronary ischemia caused by myocardial bridges.
Absence of arteriosclerosis in intramyocardial coronary arteries: A mystery to be solved?
Keywords: Coronary circulation; Endothelium; Myocardial bridging; ACE protein, human; dipeptidyl carboxypeptidase; endothelin 1; adipose tissue; coronary artery blood flow; coronary artery disease; coronary blood vessel; histology; human; metabolism; myocardial bridging; paracrine signaling; pathology; pathophysiology; physiology; prenatal development; review; vascular endothelium; Adipose Tissue; Coronary Artery Disease; Coronary Circulation; Coronary Vessels; Endothelin-1; Endothelium, Vascular; Humans; Myocardial Bridging; Paracrine Communication; Peptidyl-Dipeptidase A